2000
DOI: 10.1080/01421590078526
|View full text |Cite
|
Sign up to set email alerts
|

AMEE Guide No. 18: Standard setting in student assessment

Abstract: Licensure, credentialling and academic institutions are seeking new innovative approaches to the assessment of professional competence. Central to these recent initiatives is the need to determine standards of performance, which separate the competent from the non-competent candidate. Setting standards for performance assessment is a relatively new area of study. Consequently, there is no one recommended approach to setting standards. The goal of this guide is to familiarize the reader with the framework, prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 15 publications
3
119
0
4
Order By: Relevance
“…6 Standards may be classified as either relative (norm-referenced) or absolute (criterion-referenced). 7,8 Relative standards are expressed in terms of the performance of the cohort taking the assessment.…”
Section: What Is Standard Setting?mentioning
confidence: 99%
“…6 Standards may be classified as either relative (norm-referenced) or absolute (criterion-referenced). 7,8 Relative standards are expressed in terms of the performance of the cohort taking the assessment.…”
Section: What Is Standard Setting?mentioning
confidence: 99%
“…For the purposes of admission into a school or career track, defining a proportion of the group to pass may be necessary owing to limited available spots. Different methods of establishing a passing score are explained in detail in the Association for Medical Education in Europe guide number 18 [30].…”
Section: Score the Test And Interpret The Resultsmentioning
confidence: 99%
“…the smallest number of points obtained on the exam that confirms that a student met the requirements of a particular level. 31 However, the a priori quantitative standard for pharmacology exams underwent a posteriori revision after receiving the test results. The analysis of the required score thresholds for MCQ exams demonstrated that the "passed/failed" cut-off point was always at the same level.…”
Section: Discussionmentioning
confidence: 99%